A new species of Rhacophorus (Anura: Rhacophoridae) from Gunung Gading, Sarawak - Das, I.; Haas, A. (National University of Singapore, 2005)
A new species of rhacophorid of the genus Rhacophorus is described from Gunung Gading National Park, Sarawak, western Borneo. Rhacophorus gadingensis , new species, is compared with congeners from Borneo and other parts of southeast Asia. The new species is diagnosable in showing the following combination of characters: SVL 29.5 mm in the larger of the two specimens known; snout obtuse, slightly projecting beyond mandible; head wider than long; fingers and toes webbed; lacking nuptial pads (in males) and a dermal flap along forearm; a weak supracloacal fold; spinose calcar present; skin not co-ossified to forehead, median lingual process absent; supratympanic fold weak; dorsum brown, with a dark interorbital bar; dark brown blotches on dorsum and flanks with blue blotches